Alveolar process fractures in the permanent dentition. Part 1. Etiology and clinical characteristics. A retrospective analysis of 299 cases involving 815 teeth. Issue 6 (28th September 2015) - Andreasen, Jens Ove; Lauridsen, Eva
Abstract: Aim: To describe the etiology and clinical characteristics of alveolar process fractures treated in a regional trauma clinic. Material and method: The study is a retrospective descriptive analysis of 299 patients (180 males, 119 females; 815 permanent teeth) diagnosed with fractures of the alveolar process. Results: Violence was the overall most frequent cause of injury in men (44%), whereas the three most common causes of this type of injury in women were violence (33%), falls (32%), or traffic injuries (26%). Fracture of the alveolar process occurred most frequently in the maxilla (74%) and less frequently in the mandible (26%). The majority of the fractures involved only two teeth (57%) but occasionally involved up to seven teeth. The age at fracture ranged from 5 to 90 years; alveolar process fractures occurred most frequently between 15 and 25 years of age (43%). Concomitant soft tissue injuries were present in 73%. The most frequent location of the mandibular fracture line was along the periodontal ligament of the canine and in the sagittal suture between the two central maxillary incisors. This pattern appears to correlate with weak zones in the jaws. Conclusion: In conclusion, alveolar process fractures are rare. They occur most frequently in young males and are often associated with violence. Concomitant soft tissue injuries are frequent. This type of injury accordingly appears to result from a frontal impact transmitted through a soft tissue shield (the lips) where the zone of least resistance gives in, namely the periodontal ligament and areas where the alveolar bone is thin.